Label-Free Electrochemical Detection of S. mutans Exploiting Commercially Fabricated Printed Circuit Board Sensing Electrodes - Dutta, Gorachand (Micromachines (Basel), 2019)
This paper reports for the first time printed-circuit-board (PCB)-based label-free electrochemical detection of bacteria. The demonstrated immunosensor was implemented on a PCB sensing platform which was designed and fabricated in a standard PCB manufacturing facility. Bacteria were directly captured on the PCB sensing surface using a specific, pre-immobilized antibody. Electrochemical impedance spectra (EIS) were recorded and used to extract the charge transfer resistance (R(ct)) value for the different bacteria concentrations under investigation. As a proof-of-concept, Streptococcus mutans (S. mutans) bacteria were quantified in a phosphate buffered saline (PBS) buffer, achieving a limit of detection of 10(3) CFU/mL. Therefore, the proposed biosensor is an attractive candidate for the development of a simple and robust point-of-care diagnostic platform for bacteria identification, exhibiting good sensitivity, high selectivity, and excellent reproducibility.